Determination of nitration kinetics of p-Nitrotoluene with a homogeneously continuous microflow. (16th January 2022) - Song, Jing; Cui, Yongjin; Sheng, Lin; Wang, Yujun; Du, Chencan; Deng, Jian; Luo, Guangsheng
Highlights: The characteristics of nitration hinder the accurate determination of kinetics. Constructing a continuous-flow microreactor system to obtain kinetics of nitration. Determining p-nitrotoluene nitration kinetics by homogeneous reaction in the system. Establishing a general method to obtain the values of C NO 2 + / C HNO 3 . Abstract: The kinetics of p -nitrotoluene nitration with mixed acid is important to industrial process design and safety control. However, it's difficult to acquire accurate kinetic data and no kinetics study has ever been reported before because of fast, highly exothermic and heterogeneous characteristics. In this work, a continuous-flow microreactor system including a micromixer, a capillary reactor and an online quenching module was designed to carry out the nitration under a homogeneous reaction condition. The homogeneous nitration can completely eliminate mass transfer resistance between phases, and accurately control reaction temperature and residence time in the continuous-flow microreactor system. The observed reaction rate constants separately based on HNO3 and NO2 +, pre-exponential factor and activation energy of p -nitrotoluene nitration were obtained and a general method was established to collect kinetics data for such a kind of fast and highly exothermal nitration reactions.